Concept of privacy from Islamic perspective in flood evacuation centre - Abdul Rahim, Asiah; W Seman, Wan Mohamad Amin (PLANNING MALAYSIA, 2019)
The flood events in Kelantan during December 2014 were examples of disasters in recent years that garnered national attention. Emergencies can occur with little or no warning. Floods deprive families of basic food and shelter, and lead to significant social and emotional impacts that linger long after the event. Every year, schools and community areas have been used as evacuation centres. A number of problems faced by the evacuees have been identified, especially in terms of physical facilities such as the lack of privacy for women and families, especially during night time. The objectives of this paper are as follows: (1) to study on the concept of privacy from an Islamic Perspective; and (2) to assess privacy in the context of a flood evacuation centre. The data gathered were tabulated. The research also utilised secondary data from literature. Data were analysed using content analysis and case studies. The data were analysed based on issues raised. Recommendations and suggestion are posed on overcoming the identified issues and problems. This research contributes a review of examples of evacuation facilities that follow Islamic teaching in the context of privacy in evacuation centres.